MiRNAs in melanoma: a defined role in tumor progression and metastasis. (2nd January 2016) - Mannavola, Francesco; Tucci, Marco; Felici, Claudia; Stucci, Stefania; Silvestris, Franco
Abstract : The crosstalk of melanoma cells with components of the microenvironment promotes malignant cell proliferation and spread to distant tissues. Although the major pathogenetic events have already been elucidated, the mechanisms that drive the metastatic behavior of tumor cells are still undefined. MicroRNAs (miRNAs) are small non-coding RNAs that control post-transcriptional gene expression through interconnected kinases upstream of functional genes involved in tumor progression. Here, we review the biological relevance of melanoma-related miRNAs and focus on their potential role in propagating signals that may cause tumor microenvironment rearrangements, as well as disablement of the immune system and melanoma cell proliferation.